Brave old world. - O'Hehir, Andrew (Sight & Sound, 2001)
Deals with the continued demand for science-fiction adventure serials in television. Views of critics on the plan to launch the television program `Enterprise'; Details on the viewers of science fiction series; Information on two science fiction shows, `Andromeda' and `Earth: Final Conflict.'